2019
DOI: 10.1167/19.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding gloss perception through the lens of art: Combining perception, image analysis, and painting recipes of 17th century painted grapes

Abstract: To understand the key image features that we use to infer the glossiness of materials, we analyzed the pictorial shortcuts used by 17th century painters to imitate the optical phenomenon of specular reflections when depicting grapes. Gloss perception of painted grapes was determined via a rating experiment. We computed the contrast, blurriness, and coverage of the grapes' highlights in the paintings' images, inspired by Marlow and Anderson (2013). The highlights were manually segmented from the images, and nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 51 publications
7
36
0
Order By: Relevance
“…In previous work, Beurs' manual has supported the notion that contrast and blurriness, but not coverage of highlights, were the image features used to render the glossiness of grapes in 17th-century paintings. The grapes recipe contained in the manual also confirmed the artistic convention of using white to render highlights, thus providing an example of using key perceptual information to produce an efficient yet effective rendering of material properties (Di Cicco, Wijntjes, & Pont, 2019). We also considered Beurs' recipes for additional insights into the image features and perceptual shortcuts exploited by painters to render translucency and juiciness.…”
Section: Introductionmentioning
confidence: 83%
“…In previous work, Beurs' manual has supported the notion that contrast and blurriness, but not coverage of highlights, were the image features used to render the glossiness of grapes in 17th-century paintings. The grapes recipe contained in the manual also confirmed the artistic convention of using white to render highlights, thus providing an example of using key perceptual information to produce an efficient yet effective rendering of material properties (Di Cicco, Wijntjes, & Pont, 2019). We also considered Beurs' recipes for additional insights into the image features and perceptual shortcuts exploited by painters to render translucency and juiciness.…”
Section: Introductionmentioning
confidence: 83%
“…Instead of strictly following physics, painters have extracted the essential visual cues needed to trigger the perception of materials. Di Cicco, Wijntjes, and Pont (2019) studied visual cues for gloss, which were implicitly discussed in a painting manual by the seventeenth-century painter Willem Beurs ( Beurs, 1692 ). They found that predictors that explained a large portion of the variance in gloss perception had implicitly been described within this seventeenth-century manual.…”
Section: Introductionmentioning
confidence: 99%
“…Berzhanskaya, Swaminathan, Beck, and Mingolla (2005) later determined the extent of the induced glossy-appearing region. A very important property of a highlight is the sharpness of its border, which is positively correlated with perceived glossiness (Di Cicco, Wijntjes, & Pont, 2019;Marlow & Anderson, 2013;Sève, 1993). However, many more highlight properties, conditions that systematically influence them, and correlated changes in perceived gloss have been identified and investigated.…”
Section: Introductionmentioning
confidence: 99%